Massive Deposition and Accumulation of Hydroxyapatite Crystal after Total Hip Arthroplasty: A Case Report - Shin Yamada; Koji Nozaka; Hidetomo Saito; Hiroaki Kijima; Hiroshi Tazawa; Yasusi Takasaki; Yoichi Shimada (Case Reports in Orthopedics)
We presented a case in which massive hydroxyapatite accumulation was observed around the artificial hip joint. A 66-year-old female showed a massive accumulation of fluid in and around the hip joint, and milk-like aspirate was obtained. Her aspirate culture was negative, and sediment analysis by X-ray diffraction showed that its component was hydroxyapatite. Since pain was mild, the patient was treated conservatively. To our knowledge, this is the first case in which liquid hydroxyapatite (milk of calcium) was accumulated around the artificial hip joint.